Modeling and mapping of atmospheric mercury deposition in adirondack park, new york. - Xue Yu (Public Library of Science (PLoS), 2013)
The Adirondacks of New York State, USA is a region that is sensitive to atmospheric mercury (Hg) deposition. In this study, we estimated atmospheric Hg deposition to the Adirondacks using a new scheme that combined numerical modeling and limited experimental data. The majority of the land cover in the Adirondacks is forested with 47% of the total area deciduous, 20% coniferous and 10% mixed. We used litterfall plus throughfall deposition as the total atmospheric Hg deposition to coniferous and deciduous forests during the leaf-on period, and wet Hg deposition plus modeled atmospheric dry Hg deposition as the total Hg deposition to the deciduous forest during the leaf-off period and for the non-forested areas year-around. To estimate atmospheric dry Hg deposition we used the Big Leaf model. The average atmospheric Hg deposition to the Adirondacks was estimated as 17.4 [Formula: see text]g m[Formula: see text] yr[Formula: see text] with a range of -3.7-46.0 [Formula: see text]g m[Formula: see text] yr[Formula: see text]. Atmospheric Hg dry deposition (370 kg yr[Formula: see text]) was found to be more important than wet deposition (210 kg yr[Formula: see text]) to the entire Adirondacks (2.4 million ha). The spatial pattern showed a large variation in atmospheric Hg deposition with scattered areas in the eastern Adirondacks having total Hg deposition greater than 30 μg m(-2) yr(-1), while the southwestern and the northern areas received Hg deposition ranging from 25-30 μg m(-2) yr(-1).